Improving the use of research evidence in guideline development: 11. Incorporating considerations of cost-effectiveness, affordability and resource implications - Edejer Tessa (BMC, 2006)
Abstract Background The World Health Organization (WHO), like many other organisations around the world, has recognised the need to use more rigorous processes to ensure that health care recommendations are informed by the best available research evidence. This is the 11th of a series of 16 reviews that have been prepared as background for advice from the WHO Advisory Committee on Health Research to WHO on how to achieve this. Objectives We reviewed the literature on incorporating considerations of cost-effectiveness, affordability and resource implications in guidelines and recommendations. Methods We searched PubMed and three databases of methodological studies for existing systematic reviews and relevant methodological research. We did not conduct systematic reviews ourselves. Our conclusions are based on the available evidence, consideration of what WHO and other organisations are doing and logical arguments. Key questions and answers When is it important to incorporate cost-effectiveness, resource implications and affordability considerations in WHO guidelines (which topics)? • For cost-effectiveness: The need for cost/effectiveness information should be dictated by the specific question, of which several may be addressed in a single guideline. It is proposed that the indications for undertaking a cost-effectiveness analysis (CEA) could be a starting point for determining which recommendation(s) in the guideline would benefit from such analysis. • For resource implications/affordability: The resource implications of each individual recommendation need to be considered when implementation issues are being discussed. How can cost-effectiveness, resource implications and affordability be explicitly taken into account in WHO guidelines? • For cost-effectiveness: ∘ If data are available, the ideal time to consider cost-effectiveness is during the evidence gathering and synthesizing stage. However, because of the inconsistent availability of CEAs and the procedural difficulty associated with adjusting results from different CEAs to make them comparable, it is also possible for cost-effectiveness to be considered during the stage of developing recommendations. ∘ Depending on the quantity and quality and relevance of the data available, such data can be considered in a qualitative way or in a quantitative way, ranging from a listing of the costs to a modelling exercise. At the very least, a qualitative approach like a commentary outlining the economic issues that need to be considered is necessary. If a quantitative approach is to be used, the full model should be transparent and comprehensive. • For resource implications/affordability: ∘ Resource implications, including health system changes, for each recommendation in a WHO guideline should be explored. At the minimum, a qualitative description that can serve as a gross indicator of the amount of resources needed, relative to current practice, should be provided. How does one provide guidance in contextualizing guideline recommendations at the country level based on considerations of cost-effectiveness, resource implications and affordability? • All models should be made available and ideally are designed to allow for analysts to make changes in key parameters and reapply results in their own country. • In the global guidelines, scenarios and extensive sensitivity/uncertainty analysis can be applied. Resource implications for WHO • From the above, it is clear that guidelines development groups will need a health economist. There is need to ensure that this is included in the budget for guidelines and that there is in-house support for this as well.